PENGARUH MODAL KERJA TERHADAP PENDAPATAN PADA PT PUDJIADI AND SONS Tbk JAKARTA PERIODE 2012-2018 - GAVIEN TIARA MARLINA KINANTHI, GAVIEN TIARA MARLINA KINANTHI; Karyadi (JEBS (Journal of Economic and Business Student), 2022)
This research aims to know the influence of working capital to revenue at PT Pudjiadi And Sons Tbk Jakarta period of 2012-2018. This research method uses quantitative method. Data collection techniques are literature studies, field studies (indirectly). The analysis uses secondary data from financial statements for the period 2012-2018. Data analysis shows that the correlation coefficient is 0.877, that mean the relationship between working capital and revenue is very strong. While the coefficient of determination is 76.9% show the magnitude influence of working capital to revenue and the remaining 23.1% is influenced by other factors. From the research conducted, it was found several problems are increased business competition, weakening MICE (Meeting, Invitation, Convention, and Exhibition), many rooms are cancel due to the issue of disasters, incidental losses due to disasters, deficiency of cooperation with OTA (Online Travel Agent). The efforts made by the company are to increase cooperation with OTA (Online Travel Agent), Increase events, improve customer retention systems, conduct operational efficiency programs, and expand business. The advice given is to expand marketing strategies, make new breakthroughs in expand the business and pay more attention conditions of location to see opportunities